Analysis of Lead Time Reduction in Pre-Delivery Installation Process of Excavator Units at PT. XYZ Assembly Plant - Dibyo Setiawan; Tubagus Syah Fatahillah Gelagah Wangi Bintaran; Apri Setiawan; Hanni Maksum Ardi; Herbert Hasudungan Siahaan; Cahyo Wibowo (Universitas Negeri Jakarta, 2026)
The Pre-Delivery Installation (PDI) Department of PT. XYZ is tasked with carrying out the installation process of imported heavy equipment attachment units, including one of the leading excavator units. Obstacles that arise can affect installation productivity. The gap between the actual installation results of 78 units and the company's target of 156 units requires a solution or resolution to improve the process that can be implemented. Therefore, it is necessary to investigate the wait time associated with decreased productivity, which is the longest component of the installation process. This work has a purpose to analyze lead time of the excavator attachment unit installation process. The method is applied with a time study approach referring to data sheets and observations, then processing lead time data using pie charts, Pareto diagrams, and fishbone diagrams. Furthermore, we review the planning calendar, realization, and improvement engineering. Reduction is carried out by providing additional work personnel and procuring sanding machine tools to reduce the installation and critical time of the planning calendar. The realization condition for 562 minutes with the implementation of improvement engineering is reduced to 318 minutes. Thus, it can speed up implementation time of the excavator attachment in unit installation process to 224 minutes or 44%.